Poor long‐term prognosis in patients admitted with strong suspicion of acute myocardial infarction but discharged with another diagnosis. (16th March 2021) - Lindahl, B.; Ljung, L.; Herlitz, J.; Alfredsson, J.; Erlinge, D.; Kellerth, T.; Omerovic, E.; Ravn‐Fischer, A.; Sparv, D.; Yndigegn, T.; Svensson, P.; Östlund, O.; et al.
Abstract: Background: Characteristics and prognosis of patients admitted with strong suspicion of myocardial infarction (MI) but discharged without an MI diagnosis are not well‐described. Objectives: To compare background characteristics and cardiovascular outcomes in patients discharged with or without MI diagnosis. Methods: The DETermination of the role of Oxygen in suspected Acute Myocardial Infarction (DETO2X‐AMI) trial compared 6629 patients with strong suspicion of MI randomized to oxygen or ambient air. The main composite end‐point of this subgroup analysis was the incidence of all‐cause death, rehospitalization with MI, heart failure (HF) or stroke during a follow‐up of 2.1 years (median; range: 1–3.7 years) irrespective of randomized treatment. Results: 1619 (24%) received a non‐MI discharge diagnosis, and 5010 patients (76%) were diagnosed with MI. Groups were similar in age, but non‐MI patients were more commonly female and had more comorbidities. At thirty days, the incidence of the composite end‐point was 2.8% (45 of 1619) in non‐MI patients, compared to 5.0% (250 of 5010) in MI patients with lower incidences in all individual end‐points. However, for the long‐term follow‐up, the incidence of the composite end‐point increased in the non‐MI patients to 17.7% (286 of 1619) as compared to 16.0% (804 of 5010) in MI patients, mainly driven by a higher incidence of all‐cause death, stroke and HF. Conclusions: Patients admitted with a strong suspicion of MI but discharged with another diagnosis had more favourable outcomes in the short‐term perspective, but from one year onwards, cardiovascular outcomes and death deteriorated to a worse long‐term prognosis. Abstract :